PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WRITE AROUND UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA KELAS V SD NEGERI 5 TANJUNG PUNAK - Sulasmiana, Sulasmiana; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low ability of writing poetry of grade 5 students of SD Negeri 5 Tanjung Punak Kecamatan Rupat Utara with an average score of 65.42 (KKM 70). The purpose of this study is to improve the ability to write poetry students of class V SD Negeri 5 Tanjung Punak Kecamatan Rupat Utara, with the implementation of cooperative learning model type write a round. This study is a classroom action observer consisting of two cycles. The subjects of this study are the students of grade 5 of SD Negeri 5 Tanjung Punak Kecamatan Rupat Utara with 21 students, consisting of 13 male students and 8 female students. Based on the analysis of observation sheets, teacher activity and student activity have increased every meeting. The activity of teachers with the application of cooperative type model write a round at the first meeting of cycle one is 62.50% (good), and at the second meeting of cycle one 70,83% (good). In cycle two, teacher activity at first meeting was 83,33% (Very Good) and at second meeting 91,66% (excellent). Student activity by applying of cooperative type model write a round at first meeting of cycle one equal to 58,33 (enough), and at second meeting of cycle one 66,70% (good). In cycle two, student activity at first meeting was 87,58% (Very Good) and at second meeting 95,80% (very good). Ability to write student poems before applying cooperative learning model type write a round has an average value of 65.62, after the application of cooperative learning model type STAD average student learning outcomes increased in Daily Deuteronomy (UH) I to 72.62 and at UH II the average of students' learning achievement increased to 83.63. Based on this it can be concluded that the application of cooperative learning model type write a round can improve the ability to write poetry of grade 5 students of SD Negeri 5 Tanjung Punak Kecamatan Rupat Utara.Keywords: Cooperative type write a round model, the ability to write poetry